Clinical Effects of an Amino Acid and Glucose Solution in Non-surgical Gastrointestinal Patients of Internal Medicine - Ari Fahrial Syam; Achmad Fauzi; Murdani Abdullah; Marcellus Simadibrata; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: This study was performed to assess the efficacy and safety of intravenous amino acid and glucose solution with electrolytes in non-surgical gastrointestinal patients. Method: This single, open, and pre-post study was conducted in the internal medicine ward at Cipto Mangunkusumo Hospital between June 2007 and March 2008. Patients were administered solution of amino acid, glucose, and electrolytes via peripheral vein at a dose of 1000 mL/day for one week period. Non-operative gastroenterology patients with age between 16 and 65 years were eligible in this study; patients were excluded if they had diabetes mellitus, severe hepatic or renal dysfunction, electrolyte disturbance, and obesity. The data were analyzed by paired t-test and McNemar test using SPSS version 16. Results: Fifteen patients consisted of 8 (53.5%) female, mean age was 38.47 ± 14.73 years. The body mass index (BMI) at screening was 14.50 ± 2.11 kg/m2. Patients’ BMI increased in day-1, day-3, and day- 7 into 14.5; 14.58; 14.80 kg/m2, respectively (p 0.05). The increasing of prealbumin, albumin, transferin, and total protein were 7.30 mg/dL vs 11.16 mg/dL; p = 0.018; 2.71 g/dL vs 3.12 g/dL; p = 0.024; 102.37 mg/dL vs 141.95 mg/dL; p = 0.016; 6.24 g/dL vs 6.85 g/dL; p = 0.019, respectively. The clinical symptoms of nausea and weakness in patients decreased from 53.3% to 6.7%; p = 0.016, and 66.7% to 6.7%; p = 0.004. Conclusion: This parenteral nutrition solution was effective to improve clinical nutrition parameters. Keywords: amino acid and glucose solution, non-surgical gastrointestinal patients, peripheral parenteral nutrition